Strategic planning for Real Plaza - Catacora Flores, Cristina Celedonia; Kanamori Ogata, Claudia Eliana; Maldonado Bocangel, Evelyn María del Carmen; Vizcardo Medina, Marco Augusto (Pontificia Universidad Católica del Perú, 2019)
The purpose of this thesis was to formulate a five year Strategic Plan for Real Plaza, covering the period 2019 to 2024. Real Plaza is the largest chain of shopping centers in Peru, an industry where many different trends are modifying the external environment, such as the increasing importance of e-commerce and environmental conservation, which are changing the whole industry and also demanding changes in the strategy of the company while reinforcing the importance of strengthening Real Plaza’s competitive advantage to compete through a differentiation strategy in the industry. The Sequential Model of the Strategic Process was used to formulate this Plan (D’Alessio, 2013). The main result of the Strategic Process shows the need for Real Plaza to develop a differentiation strategy to achieve the proposed vision for 2024 in eight major areas: (a) Financial performance, (b) Market penetration, (c) Brand recognition, (d) Mix of tenants, (e) Innovation, (f) Corporate Social Responsibility, (g) Digital transformation, and (h) Organizational Culture. Eleven strategies were retained (a) Increase penetration, (b) Increase market share, (c) Augment the quality and variety of stores, (d) Position the brand as entertainment centers for the family, (e) Create an omni-channel strategy, (f) Increase productivity of employees, (g) Brand loyalty, (h) Be environmentally and social responsible, (i) Diversify offering, (j) Transform shopping centers to entertainment centers, and (k) Strategic alliances to support the community.
Keywords: Planificación financiera; Planificación estratégica; https://purl.org/pe-repo/ocde/ford#5.02.04